Assessment of Risk of Establishment of Wheat Dwarf Bunt (Tilletia controversa) in China - Wen-mmg JIA; Yi-lin ZHOU; Xia-yu DUAN; Yong LUO; Sheng-li DING; Xue-ren CAO; D L Fitt Bruce (Journal of Integrative Agriculture, 2013)
Wheat dwarf bunt, caused by Tilletia controversa Kühn (TCK), is an important quarantine wheat disease throughout the world. Based on published research results of the biology and the epidemiology of the disease, the main factors including temperature, humidity, snow cover, and their parameters relating to teliospore germination, infection and epidemics of TCK were determined. The geophytopathological models for the risk analysis of wheat dwarf bunt establishment were modified. Fifty-year meteorologic data from about 500 weather stations in China were used to calculate the probabilities of TCK establishment in different geographic sites with the models. The map that displays the establishment risk of TCK in winter wheat growing regions in China was generated by using geographical information system (GIS). The zones showing high, moderate, low, and very low, including no risk, of TCK establishment accounted for 27.33, 27.69, 38.12, and 6.86% of total winter wheat growing areas in China, respectively. These results will provide useful information to formulate quarantine regulations and wheat importation policy in China.